Ultra‐low‐noise 1 µm optical frequency comb. Issue 17 (1st August 2014) - Kundermann, S.; Portuondo‐Campa, E.; Lecomte, S.
Abstract : A robust optical frequency comb is realised with an Origami‐10 mode‐locked femtosecond laser from Onefive GmbH generating a 100 MHz pulse train at a centre wavelength of 1047 nm. The carrier‐envelope offset frequency has been stabilised to a record level contributing to relative fluctuations of the optical carrier frequency of 1.1 × 10 −18 at 1 s and averaging down to the 10 −22 level at 10 000 s. Cycle‐slip free carrier‐envelope offset frequency stabilisation has been routinely achieved over 10 h. Ultra‐low relative intensity noise has been measured as well and makes such a system very attractive for demanding applications where low noise and high reliability are requested.